Behind the change in Turkish foreign policy vis-à-vis Cyprus between 2002 and 2004: the impact of leadership and the EU - Kamburoğlu, İnanç (2015)
This thesis attempts to explain the change in Turkey’s foreign policy regarding Cyprus between 2002 and 2004. It argues that the overriding factor in this policy change was a change in leadership, i.e., the coming to power of the Justice and Development Party (AKP), which developed a decidedly liberal outlook on foreign affairs following its split in 2001 from the anti-Western, Islamist Welfare Party. Other crucial determinants included the Europeanization of the Cyprus issue and selective support for interest groups within Turkey, both of which were affected to various degrees by the European Union and a propitious change in decision-making context.